Cellular and humoral immunity in male homosexuals in Istanbul - (:unkn) unknown (My University, 1987)
In this study, a total of 68 male homosexuals working as prostitutes and 36 control cases of symptom free health care workers were investigated between December 1985 and June 1986. Differential white cell count, E rosette formation and theophylline treated E rosette formation, EAC rosette assay, surface immunoglobulin expression and skin tests with purified protein derivative (ppD), phytohemagglutinin (PHA), and streptokinase-streptodornase (SK-SD) were performed on each participant. HBsAg and total antibodies against HBsAg, HIV, CMV, HSV and Ig G, Ig A and Ig M levels were measured. The humoral and cellular immune parameters for each group were compared. There was no HIV antibody positivity. There were no statistical differences between groups other than the serum Ig M levels. When homosexual subgroups, according to their sexual practices and use of illicit drugs, were compared for humoral and cellular immune parameters there were no statistically significant differences between them.